CRISPR-Cas13-Mediated Knockdown of lncRNA-GACAT3 Inhibited Cell Proliferation and Motility, and Induced Apoptosis by Increasing p21, Bax, and E-Cadherin Expression in Bladder Cancer - Zhang, Zhongfu; Chen, Jieqing; Zhu, Zhongshuang; Zhu, Zhongqing; Liao, Xinhui; Wu, Jianting; Cheng, Jianli; Zhang, Xintao; Mei, Hongbing; Yang, Guosheng (Frontiers in Molecular Biosciences, 2021)
The current study is to investigate the expression pattern and biological function of long non-coding RNA Focally gastric cancer-associated transcript3 (GACAT3) in bladder cancer. Real-time quantitative qPCR was used to detect the expression level of GACAT-3 in tumor tissues and paired normal tissues. Human bladder cancer T24 and 5637 cell lines were transiently transfected with specific CRISPR-Cas13 or negative control CRISPR-Cas13. Cell migration, proliferation and apoptosis were measured by using wound healing assay CCK-8 assay and Caspase-3 ELISA assay, respectively. The expression changes of p21, Bax and E-cadherin after knockdown of GACAT3 were detected by using Western blot. The results demonstrated that GACAT3 was up-regulated in bladder cancer tissues than that in the paired normal tissues. Inhibition of cell proliferation, increased apoptosis, and decreased motility were observed in T24 and 5637 cell lines transfected by CRISPR-Cas13 targeting GACAT3. Downregulation of GACAT3 increased p21, Bax and E-cadherin expression and silencing these genes could eliminate the phenotypic changes induced by knockdown of GACAT3. A ceRNA mechanism for GACAT3 was also revealed. By using CRISPR-Cas13 biotechnology, we suggested that GACAT3 may be a novel target for diagnosis and treatment of bladder cancer.